The International Deep Brain Stimulation Registry and Database for Gilles de la Tourette Syndrome: How Does It Work? - Deeb, Wissam; Rossi, Peter J.; Porta, Mauro; Visser-Vandewalle, Veerle; Servello, Domenico; Silburn, Peter; Coyne, Terry; Leckman, James F.; Foltynie, Thomas; Hariz, Marwan; Joyce, Eileen M.; Zrinzo, Ludvic; et al. (Frontiers in Neuroscience, 2016)
Tourette Syndrome (TS) is a neuropsychiatric disease characterized by a combination of motor and vocal tics. Deep brain stimulation (DBS), already widely utilized for Parkinson’s disease and other movement disorders, is an emerging therapy for select and severe cases of TS that are resistant to medication and behavioral therapy. Over the last two decades, DBS has been used experimentally to manage severe TS cases. The results of case reports and small case series have been variable but in general positive. The reported interventions have, however, been variable, and there remain non-standardized selection criteria, various brain targets, differences in hardware, as well as variability in the programming parameters utilized. DBS centers perform only a handful of TS DBS cases each year, making large-scale outcomes difficult to study and to interpret. These limitations, coupled with the variable effect of surgery, and the overall small numbers of TS patients with implanted DBS worldwide, have delayed regulatory agency approval (e.g. FDA and equivalent agencies around the world). The Tourette Association of America, in response to the worldwide need for a more organized and collaborative effort, launched an international TS DBS registry and database. The main goal of the project has been to share data, uncover best practices, improve outcomes, and to provide critical information to regulatory agencies. The international registry and database has improved the communication and collaboration among TS DBS centers worldwide. In this paper we will review some of the key operation details for the international TS DBS database and registry.